2019
DOI: 10.1590/1809-4430-eng.agric.v39nep74-84/2019
|View full text |Cite
|
Sign up to set email alerts
|

TEMPORAL VARIATION AND SPATIAL DISTRIBUTION OF RELATIVE INDICES OF LEAF CHLOROPHYLL IN GRAPEVINE cv. CHARDONNAY

Abstract: Variation in the spatial distribution of leaf chlorophyll content associated with the progression of the phenological cycle of crops may occur in cultivated areas as a result of the variability of environmental conditions and of the intrinsic properties of the plants. The objective of the present study was to model the trend in variation and assess the temporal stability of index of chlorophyll a, b, and total chlorophyll (Chla, Chlb, and Chlt, respectively), and to characterize the spatial distribution of Chl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…However, Costa et al (2019) observed in the same Chardonnay vineyard that the chlorophyll content increased until the last evaluation at 120 dap in 2017 season, when maturation was completed. This divergent behavior can be explained by the climatic condition in which the vines evaluated by Costa et al (2019) were exposed, since it is a tropical climate with high solar incidence during almost the entire growing season.…”
Section: Calibration and Validation Proceduresmentioning
confidence: 84%
See 1 more Smart Citation
“…However, Costa et al (2019) observed in the same Chardonnay vineyard that the chlorophyll content increased until the last evaluation at 120 dap in 2017 season, when maturation was completed. This divergent behavior can be explained by the climatic condition in which the vines evaluated by Costa et al (2019) were exposed, since it is a tropical climate with high solar incidence during almost the entire growing season.…”
Section: Calibration and Validation Proceduresmentioning
confidence: 84%
“…Chl meters measure leaf absorbance at red and near-infrared wavelengths as chlorophylls strongly absorb the red light. The use of hand-held Chl meters makes possible to estimate both the leaf Chl and N contents through the fitting of models, providing a simple, low cost, fast and non-destructive field measurement, saving time and labor (Parry;Blonquist Jr;Bugbee, 2014;Kalaji et al, 2017;Brito et al, 2011;Rigon et al, 2013;Xiong et al, 2015;Costa et al, 2019;Walker et al, 2021).…”
Section: Introductionmentioning
confidence: 99%